Online Trade of Clothes in the Context of the Green Economy - Marin, Georgiana-Ionela; Mecu, Andra-Nicoleta; Chițu, Florentina; Turtureanu, Anca (Acta Universitatis Danubius. Œconomica, 2022)
Over the last fifteen years, the concept of the „green economy” has started to be given increasing importance not only in academia, but also in the implementation of various public policies, as a result of the need to respect sustainable development. Given the increased importance of respecting the environment in the current context, this article aims to highlight the impact of online trade in clothing sector on the consumer in terms of sustainability. Through an opinion poll, young people's perception of the impact of online clothes trade in the context of the COVID-19 pandemic was investigated, reaching the conclusion that the pandemic led to a change in behavioral trends with regard to the acquisition of clothing.